Serum Magnesium is Inversely Associated with Body Composition and Metabolic Syndrome - AlMaha Al Shammaa (17986690) (2023)
Purpose Magnesium is vital to maintain normal physiological functions. We aimed to identify the association between serum magnesium and different measures of body adiposity among Qatari adults. We hypothesized that the association was mediated by depression and sleep duration. Patients and Methods The study included 1000 adults aged 20 years and above who attended the Qatar Biobank Study (QBB) between 2012 and 2019. Body adiposity was assessed using dual-energy X-ray absorptiometry (DEXA). Serum magnesium concentration was measured. Sub-optimal magnesium was defined as magnesium concentration less than 0.85 mmol/L. The association was examined using linear regression. Results The mean age of the participants (n=1000) was 35.8 (SD 10.3) years. More than half of the participants had sub-optimal magnesium concentrations (60.2% in men and 52.3% in women). Serum magnesium was inversely associated with different types of fat mass. In the fully adjusted model, per 1 SD increment of serum magnesium had standardized regression coefficients of −0.09 (p 0.005) for total fat mass, −0.08 (p 0.008) for trunk fat, −0.09 (p 0.003) for gynoid fat and −0.08 (p 0.008) for android fat. There was no gender difference in the association. The inverse association between serum magnesium and fat mass was significant in those with sleep duration ≥7 hours but not in those <7 hours. Depressive symptom and sleep did not mediate the association between serum magnesium and fat mass. Serum magnesium was inversely associated with metabolic syndrome (per 1 SD increment had an odds ratio (OR) of 0.70 (95% CI 0.57–0.85)). Conclusion There was an inverse association between serum magnesium and fat mass, especially among those with an adequate sleep duration and without chronic conditions including diabetes, hypertension and depression. Other Information Published in: Diabetes, Metabolic Syndrome and Obesity License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/dmso.s391369